ANALISIS AKURASI DIAGNOSTIC POCKET PADA PARAMETER SPO₂, BPM, DAN SUHU TUBUH - Sofie, Mohamad; Ichsan Widiyana; Bayu Wahyudi (Elektrika, 2025)
The development of accurate and affordable IoT-based diagnostic tools is crucial for advancing healthcare services. This study aims to evaluate the performance of a Diagnostic Pocket device (n=54) in measuring body temperature, oxygen saturation (SpO₂), and heart rate (BPM) by comparing it against standard equipment (thermogun and pulse oximeter). Statistical analysis was performed using paired t-test or Wilcoxon signed-rank test for difference significance, Bland-Altman analysis for agreement level, and Pearson/Spearman correlation for the strength of the relationship. The results indicate that the Diagnostic Pocket performs well in measuring SpO₂ (Bias = +1.6%, LOA = -3.9% to +5.9%, ρ > 0.8, p > 0.05) and BPM (Bias = +5.8 BPM, LOA = -5.8 BPM to +17.4 BPM, ρ ≈ 0.6-0.7, p > 0.05), demonstrating adequate agreement and correlation with the standard device. However, for temperature measurement, the device showed a statistically significant difference (Bias = 0.1°C, LOA = -1.1°C to +0.9°C, ρ ≈ 0.4-0.6, p < 0.05) and low agreement. The disparity in temperature readings is suspected to be due to differences in sensor sensitivity, calibration, or measurement location. Variations in BPM may be influenced by the subject's physiological condition or movement. In conclusion, the Diagnostic Pocket shows promise for SpO₂ and BPM monitoring but requires further refinement of its temperature sensor component.Keywords: Diagnostic Pocket, IoT, SpO2, BPM, Pulse Oximeter ABSTRAKPengembangan alat diagnostik berbasis IoT yang akurat dan terjangkau sangat penting untuk memajukan layanan kesehatan. Penelitian ini bertujuan untuk mengevaluasi kinerja alat Diagnostic Pocket (n=54) dalam mengukur suhu tubuh, saturasi oksigen (SpO₂), dan denyut jantung (BPM) dengan membandingkannya terhadap alat standar (thermogun dan pulse oximeter). Analisis statistik dilakukan menggunakan uji paired t-test atau Wilcoxon signed-rank test untuk signifikansi perbedaan, analisis Bland-Altman untuk menilai tingkat kesepakatan, dan korelasi Pearson/Spearman untuk kekuatan hubungan. Hasil penelitian menunjukkan bahwa Diagnostic Pocket memiliki kinerja yang baik dalam mengukur SpO₂ (Bias = +1,6%, LOA = -3,9% hingga +5,9%, ρ > 0,8, p > 0,05) dan BPM (Bias = +5,8 BPM, LOA = -5,8 BPM hingga +17,4 BPM, ρ ≈ 0,60,7, p > 0,05), dengan tingkat kesepakatan dan korelasi yang memadai terhadap alat standar. Namun, untuk pengukuran suhu, alat ini masih menunjukkan perbedaan yang signifikan secara statistik (Bias = -0,1°C, LOA = -1,1°C hingga +0,9°C, ρ ≈ 0,40,6, p < 0,05) dan kesepakatan yang rendah. Disparitas pada pengukuran suhu diduga disebabkan oleh perbedaan sensitivitas sensor, kalibrasi, atau lokasi pengukuran. Variasi pada BPM mungkin dipengaruhi oleh kondisi fisiologis subjek atau gerakan. Simpulannya, Diagnostic Pocket menjanjikan untuk pemantauan SpO₂ dan BPM, namun diperlukan penyempurnaan lebih lanjut pada komponen sensor suhunya.